If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1(m + 10) = 60 Reorder the terms: 4x + -1(10 + m) = 60 4x + (10 * -1 + m * -1) = 60 4x + (-10 + -1m) = 60 Reorder the terms: -10 + -1m + 4x = 60 Solving -10 + -1m + 4x = 60 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10' to each side of the equation. -10 + -1m + 10 + 4x = 60 + 10 Reorder the terms: -10 + 10 + -1m + 4x = 60 + 10 Combine like terms: -10 + 10 = 0 0 + -1m + 4x = 60 + 10 -1m + 4x = 60 + 10 Combine like terms: 60 + 10 = 70 -1m + 4x = 70 Add '-4x' to each side of the equation. -1m + 4x + -4x = 70 + -4x Combine like terms: 4x + -4x = 0 -1m + 0 = 70 + -4x -1m = 70 + -4x Divide each side by '-1'. m = -70 + 4x Simplifying m = -70 + 4x
| -9(-4)+7=25+2 | | 2(a+6)=22 | | 63/(x+2) | | -38/3=10/9y | | 4x^2-3x+11=9x+6 | | 5(2x+3)-2(x-4)=2x-1 | | 2(x+2)(x-4)4=0 | | -34=42+-4v | | (X+3)(X+4)(X+5)=0 | | (X-3)(Y+7)=0 | | 6(5-2y)-5(y+3)= | | 5x-(x-18)=6-2(x+15) | | x*(x+1)(x+2)(x+3)=0.5625 | | 4(2+3)-2y= | | X^3-3x^2+x+1=0 | | -16-8(2a+3)=23-2a | | 4(2+3)-2y=3(4y+3) | | -14x^3+9x^2-2=0 | | 3/2x=189/20 | | -19x+4=0 | | 2(4w-1)=-10(w-3)+4 | | 5(x+5)=27 | | 30-5x=-5 | | 3.14*x^5-6x^4-9=0 | | pi*x^5-6x^4-9=0 | | 5x+5=137-6x | | 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 |